Les corps comme preuve. Médecins et inquisiteurs dans les pratiques judiciaires du Saint-Office - Federico Barbierato (L'Atelier du CRH)
The essay will start from the case of early modern Venice and focus on the strategies by which inquisitors observed and tested the bodies of witnesses and defendants. The body becomes a source of evidence that, with the help of physicians and surgeons, undergoes examination: on one hand gesture and attitudes are investigated in order to verify discourses, on the other hand recourse to torture, albeit limited, puts into play the body, which becomes the space where truth is measured.